Innovative Educational Technologies in the Educational Process - Karimova Gulshod Mamatkadirovna (Genius Journals, 2022)
In modern society, innovation technologies expand to almost every field of human activity, including such wide field as education. Innovation in education is a highly contentious issue. Education is sometimes perceived as one of the most conservative social systems and public policy fields.
Keywords: education; innovation educational technologies; learning; pedagogical innovation theory